Use of Probiotics as Prophylaxis for Postoperative Infections of Under- 5 Children Following Gastrointestinal Surgery (Journal of Paediatric Surgeons of Bangladesh, 2015)
Background: Bacterial infection is a frequent complication following operations in the gastrointestinal tract. Despite prophylactic administration of antibiotics the incidence of postoperative infections ranges from 10%30% in resection surgery.1 Most infections are caused by bacteria of enteric origin.2 In spite of restricted use of prophylactic antibiotics, the emergence of antibiotic resistance has increased significantly.3 Probiotics when consumed in adequate amounts, confer a health benefit on the host. In vitro, studies suggest that probiotics potentially act favorably on the host through several different mechanisms. They have an antimicrobial effect. Furthermore, administration of probiotics suppresses growth of potentially pathogenic microorganisms, e.g., E. coli and Enterobacteriaceae. The effects of these agents may go beyond the gastrointestinal tract to distant areas, such as the urogenital and respiratory mucosa. It has been hypothesized by several authors that these characteristics can be used in a clinical setting of preoperative prophylaxis for reduction of postoperative infections. Preoperative antibiotic prophylaxis constitutes more than 10% of antibiotic usage in surgery and a reduction could lead to a reduced pressure on development of antibiotic resistance. It may therefore be of interest to study if probiotics may be used in the preoperative preparation of patients undergoing gastrointestinal operations.Objective: The overall objective of this study is to evaluate the effectiveness of probiotics as prophylaxis for post operative infections in under-5 children undergoing gastrointestinal surgery. Materials and methods: We are conducting a prospective comparative study with the intention to observe the postoperative periods of 60 purposively selected patients of gastrointestinal surgery in the Department of Pediatric surgery, Dhaka Medical College Hospital (DMCH), Dhaka, over a period of 18 months from October, 2013 to March, 2015. The patients are going to be divided into 2 groups by random sampling- Group A (Control group- without probiotics) and Group B (Study group- with probiotics). Under-5 children are planned to be selected as study subjects. All children are subjected to investigate for white blood cell (WBC) count and Creactive protein (CRP) preoperatively and on 5th postoperative day (POD) in addition to routine investigations. Structured questionnaire is used to collect information regarding fever, surgical site infection, WBC and CRP count before operation and 5 days after operation (i.e. on 5th POD). Informed written consent from parents or legal guardian is taken after describing the study objectives. Ethical clearance has been sought from the Ethical Committee of Dhaka Medical CollegeResults: Total 8 patients are studied till now, 4 in each group. From this limited data we have observed that there has been apparently minimum difference between the cases and controls regarding postoperative infections.Discussion: Post operative wound infections are quite common and an important reason for administering antibiotics for prolonged periods.13 Probiotics given preoperatively tends to reduce the incidence of post operative infection, though the accurate mechanism is not known. The use in patients undergoing colorectal surgery does not seem to show any benefit.18 The result of our study until now has not demonstrated any added benefit of prophylactic use of probiotis in the specified age group. So up to now the available data is compatible with the various data seen in other studies.18 In our study, it is very early to comment on the results.Conclusion: This is an on-going study. Definite conclusion could not be drawn at this preliminary stageJ. Paediatr. Surg. Bangladesh 4(2): 38-43, 2013 (July)